(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: There is strong evidence on the potential of the Community Based Health Insurance (CBHI) schemes to facilitate access to healthcare and offer financial protection against the cost of illness for people excluded from formal insurance systems. However, enrollment in the Family Health Insurance scheme has remained low and there has been substantial dropout from the initial enrollment of the scheme’s insured members. Aim:This research aimed at exploring factors influencing enrollment of community members in a CBHI scheme. Methods:A mixed methods case studycomprisingqualitative phase of 10 Key Informant Interviews and 18 In-depth Interviews, and quantitative phase of 190 households: 96 insured and 94 uninsured were involved. Qualitative analysis was done using open coding while descriptive analysis was done for quantitative data. Results:Lack of awareness regarding insurance, lack of trust in management, unaffordability of insurance premiums, limited coverage of services in insurance plans, ambiguity regarding pre-existing conditions, negative marketing by drop-outs, and exclusion of vulnerable groups were some of the common reasons among uninsured group. Insured members of the scheme also had little knowledge about the scheme. Conclusions:The major reason for enrollment was the influence of community leader’s guidance. Stakeholders believed in modification of marketing strategies and innovations in increasing community awareness. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.293-301